Combine treatment of Sofosbuvir and Velpatasvir in Patients of Chronic Hapatitis C - Waseem Babur, Naveed Noor Khan, Syed Meerab Javed, Zille-Huma, Fayaz Ahmed Memon, Abdul Azeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to evaluate how well individuals with chronic hepatitis C respond to a combination treatment consisting of sofosbuvir and velpatasvir. Study Design: Observational/ Prospective study Place of Study: King Salman Armed Forces Hospital Tabuk KSA and Dow University of Health Sciences Karachi Pakistan. Duration of Study: Jan, 2021 to Dec, 2021 Methods: This research included 42 participants of both sexes. Patients ranged in age from 20 to 78. After obtaining written permission, we collected demographic data about the patient, including age, gender, and height and weight. Patients with known genotypes of hepatitis C were presented. Patients were treated for 15 weeks with a SOF/VLP regimen that included sofosbuvir and velpatasvir. SPSS 24.0 version was used to analyse all of the data. Results: There were majority males in this study. The mean age of the cases was 33.8±7.43 years with mean BMI 23.18±7.31 kg/m2. Comorbidities were HTN, DM and obesity among all cases. There were 12 (28.6%) patients had treatment experienced. Frequency of effectiveness was found among 40 (95.2%) cases and 2 (4.8%) patients were died. Post-treatment, we found significantly improvement in aspartate aminotransferase (AST) 36.11 ± 9.13, alanine aminotransferase (ALT) 27.23 ± 11.45 and hemoglobin level 13.8 ± 4.19. Conclusion: The results of this trial led us to the conclusion that the combination therapy of hepatitis C patients with sofosbuvir and velpatasvir was successful, safe, and well tolerated by the patients.